Dispute Resolution Strategies in Construction Projects to Mitigate Impacts on Time Performance – Project Owner's Perspective - Barnado, Gito; Andhika Karim, Rully (Publisher Cv. Inara, 2024)
Abstract Disputes in the global construction industry are increasing every year. This is also in line with what is happening in the Indonesian construction industry. PT. XYZ, one of the pulp and paper producers in Indonesia., was the project owner of 128 construction contracts for the company's production facility development services from 2015 to 2021, had experiencing disputes on 45 of those contracts or 35.2% of the total construction contract services. The trend on time taken to resolve those disputes was observed to be 16.38 months on average, which was considered too long. The delay in handling these disputes will result in losses for both the owner and the contractors. The purpose of this study is to analyze the strategy of selecting dispute resolution methods for each identified cause of disputes in the construction industry in Indonesia. This study has identified 13 causes of disputes and 10 dispute resolution methods in Indonesia. A survey questionnaire that using Pair Comparison Analysis has been sent to professionals in the construction industry in Indonesia, questioning about their preference of dispute resolution method for every cause of dispute. The results of the data analysis show that there is a difference process in the dispute resolution methods for each cause of dispute. Although, Negotiation predominantly first ranks in dispute resolution. Meanwhile, for all causes of disputes, all respondents have an agreement that Arbitration and Litigation are the last methods in dispute resolution method in the construction industry in Indonesia. Keywords: Disputes; claims; sources of disputes; disputes resolution methods; time taken to resolve disputes, construction industry; Indonesia